Mia Korpiola (ed.): Nordic Perspectives on Medieval Canon Law. (Publications of Matthias Calonius Society, II, University of Helsinki, 1999). 166 s. - Villads Jensen, Kurt (Historie/Jyske Samlinger, 2000)
-